(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
This article examines the role of interactive educational technologies in developing the professional creativity of future teachers. The study is based on pedagogical, psychological and methodological approaches that interpret creativity as a professionally significant quality of a teacher. The article analyzes how interactive methods such as problem-based learning, project work, debates, case studies, role-playing, collaborative tasks and digital platforms influence the formation of creative thinking, pedagogical initiative and reflective competence. Special attention is paid to the connection between interactive learning and the development of flexible pedagogical thinking, communication culture and innovative professional behavior. The article concludes that interactive educational technologies are an important factor in preparing future teachers for modern educational challenges